Examining strategies to increase student evaluation of teaching completion rates. Issue 3 (3rd April 2021) - Lipsey, Nikolette; Shepperd, James
Abstract: Student evaluations of teaching (SETs) can provide valuable assessment information. However, online administration of SETs has corresponded with lower SET completion rates. We examined perceptions of strategies for increasing SET completion rates and the effect of offering psychological prompts (completion goals, reminders, progress feedback) and micro-incentives (-extra credit that has a negligible effect on student grades) on SET completion rates, grades, and student evaluations. Study one ( N = 469 instructors) revealed that instructors who used incentive-based strategies (compared with instructors who did not) rated such strategies as more ethical and more effective, and reported greater likelihood of using incentive-based strategies in the future. Examination of student records revealed higher SET completion rates among instructors who offered micro-incentives than among instructors who did not. In Study two ( N = 36 instructors), we randomly assigned instructors to one of three conditions: psychological prompts, micro-incentives plus prompts, or a no-information standard-practice control condition. SET completion rates were lowest in the control condition (53.9%), followed by the prompts (64.5%) and micro-incentives plus prompts (79.7%) conditions. The two experimental conditions did not differ in completion rates, but only micro-incentives differed significantly from the control. These results demonstrate that prompts and incentives are promising methods for increasing SET completion rates.